2022
DOI: 10.1007/s00432-022-03947-w
|View full text |Cite
|
Sign up to set email alerts
|

Water therapies (hydrotherapy, balneotherapy or aqua therapy) for patients with cancer: a systematic review

Abstract: Background Water therapies as hydrotherapy, balneotherapy or aqua therapy are often used in the relief of disease- and treatment-associated symptoms of cancer patients. Yet, a systematic review for the evidence of water therapy including all cancer entities has not been conducted to date. Purpose Oncological patients often suffer from symptoms which in patients with other diseases are successfully treated with water therapy. We want to gather more informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Reger et al conducted a systematic review, published in 2022, of 430 cancer patients aged 18–78 composed of 378 women and 52 men. Patients with breast cancer (n = 206, 4 studies) and gynecological cancer (n = 113, 3 studies) predominated; patients with colorectal cancer (n = 40, 1 study) and a mixed group of patients with various cancers (bladder, prostate, lung, liver) (n = 38, 2 studies) were also included [ 68 ]. The most frequently used intervention was represented by aquatic exercises such as aquatic lymphatic therapy, including aerobic exercises, mobilizations and stretching in pools of water, partial foot baths or general baths.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reger et al conducted a systematic review, published in 2022, of 430 cancer patients aged 18–78 composed of 378 women and 52 men. Patients with breast cancer (n = 206, 4 studies) and gynecological cancer (n = 113, 3 studies) predominated; patients with colorectal cancer (n = 40, 1 study) and a mixed group of patients with various cancers (bladder, prostate, lung, liver) (n = 38, 2 studies) were also included [ 68 ]. The most frequently used intervention was represented by aquatic exercises such as aquatic lymphatic therapy, including aerobic exercises, mobilizations and stretching in pools of water, partial foot baths or general baths.…”
Section: Resultsmentioning
confidence: 99%
“…not for passive mobilizations. Future studies are needed regarding the safety of using mineral waters with high temperatures [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odynets et al [ 17 ] found that a 12-week program of water-based exercise was better than pilates for active shoulder ROM and upper limb lymphedema but did not report significant differences in upper limb strength between the two groups. Water therapies have been long studied for the treatment of different pathologies including cancer related symptoms [ 38 ]. The capacity of cold water to induce peripheral vasoconstriction followed by vasodilatation as well as the massaging effect have been used to help alleviate lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic training, resistance training [ 25 ], interventions based on flexibility, yoga, tai chi, qigong, and Pilates [ 26 ], or exercise in general [ 27 ], have been proposed, with different outcomes and conclusions. Despite the large number of studies on this topic, heterogeneity in the results and methodological limitations have made the findings of the studies limited [ 28 ]. This confusion on the effects of physical-activity interventions on BC symptoms makes it necessary to deeply investigate the topic [ 29 ] to also understand the magnitude of the positive effects of physical activity among BC survivors [ 30 ].…”
Section: Introductionmentioning
confidence: 99%